INTERAKSI KETENAGAKERJAAN MUSLIM DENGAN NON-MUSLIM DALAM STUDI KOMPARATIF LINTAS MAZHAB - Ali Imron; Nurinayah Nurinayah; Nursalam Rahmatullah (Jurnal Al-Kharaj: Studi Ekonomi Syariah, Muamalah, dan Hukum Ekonomi, 2026)
Today's global reality, employment interaction between Muslims and non-Muslims is a necessity, given the dominance of non-Muslims in the industrial sector which opens up extensive employment opportunities for Muslims. However, this raises legal and ethical challenges from the perspective of Islamic Sharia, especially regarding the legality of wages and honor of Muslims in employment relations. This research aims to examine the Sharia provisions on employment interactions between Muslims and non-Muslims with a comparative study approach across fiqh schools. The methodology used is qualitative-descriptive library research with thematic analysis of the opinions of the four major schools of thought (Hanafi, Maliki, Shafi'i, and Hanbali). The results show that work interaction is permissible provided that the work does not contradict the principles of Sharia, does not support immorality or hostility towards Islam, and does not degrade the dignity of Muslims. The Mazhab differ in their views on service work (such as domestic help) for non-Muslims, but tend to allow general work (such as labor and construction), especially in cases of emergency or public benefit. This study concludes the importance of shar'i boundaries in interfaith working relationships to maintain the integrity of the akidah and the dignity of Muslims in a multicultural social structure.